Monoaminergic Modulation of Cortical Excitability - Tseng, Kuei-Yuan.; Atzori, Marco; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Monoaminergic Modulation of Cortical Excitability serves as an integrative and comprehensive comparison of the diverse and complex modulatory action of dopamine, noradrenaline, and serotonin receptors in the cortex. The volume is organized into several sections offering a broad spectrum of opinions on how the monoamine systems affect cortical function from a cellular/sub-cellular level to a system level. The complexity of these interactions are discussed in light of recent data showing how disruption of these systems dramatically affects the memory formation and information processing in the cortex. About the Editors: Dr. Kuei Y. Tseng is Assistant Professor in the Department of Cellular and Molecular Pharmacology at Rosalind Franklin University of Medicine and Science, The Chicago Medical School, North Chicago, IL, USA. Dr. Marco Atzori is Assistant Professor at the School for Behavioral and Brain Sciences at the University of Texas, Dallas, TX, USA.
Anatomical Studies of the Monoaminergic System -- The Discovery of Multiple Serotonin Receptor Subtypes: A Lesson from Molecular Cloning to Functional Expression -- Distribution of D1-Like and D2 Receptors in the Monkey Brain: Implications for Cognitive Function in Schizophrenia -- Anatomical Characteristics of Norepinephrine Axons in the Prefrontal Cortex: Unexpected Findings That May Indicate Low Activity State in Naïve Animals -- Monoaminergic Regulation of Cortical Function -- Serotonin Modulation of Cortical Activity -- Serotonergic Regulation of NMDA Receptor Trafficking and Function in Prefrontal Cortex -- Cross-Modulation Between GABAB and 5-HT Receptors: A Link Between Anxiety and Depression? -- Serotonin Involvement in Plasticity of the Visual Cortex -- Cellular Mechanisms of Working Memory and its Modulation by Dopamine in the Prefrontal Cortex of Primates and Rats -- Dopamine D1 and Glutamate N-Methyl-D-Aspartate Receptors: An Essential Interplay in Prefrontal Cortex Synaptic Plasticity -- Prefrontal Cortical Synaptic Plasticity: The Roles of Dopamine and Implication for Schizophrenia -- Acquiring the Excitatory and the Inhibitory Action of Dopamine in the Prefrontal Cortex During Postnatal Development -- Dopamine and Noradrenaline Coupling in the Cerebral Cortex -- Regulation of Cortical Functions by the Central Noradrenergic System: Emerging Properties from an Old Friend -- Neuromodulation of Cortical Synaptic Plasticity -- Computational Analyses of Cortical Monoaminergic Function -- Dopaminergic Modulation of Prefrontal Cortex Network Dynamics -- Stable and Unstable Activation of the Prefrontal Cortex with Dopaminergic Modulation -- Dopamine and Norepinephrine Modulation of Cortical and Subcortical Dynamics During Visuomotor Learning -- Monoamines and Psychiatric Disorders -- Basal Ganglia – Cortex Interactions: Regulation of Cortical Function by D1 Dopamine Receptors in the Striatum -- Interplay Between Dopamine and Acetylcholine in the Modulation of Attention -- Monoamine-Based Treatments in Schizophrenia: Time to Change the Paradigm? -- Prefrontal Cortical Circuits and Schizophrenia Pathophysiology.
Keywords: Neurosciences; Neurobiology; Neurology .; Neurosciences; Neurobiology; Neurology